Yarrowia lipolytica as a promising protein source for Pacific white shrimp (Litopenaeus vannamei) diet: impact on growth performance, metabolism, antioxidant capacity, and apparent digestibility - Zhang, Lei; Zhang, Pian; Tan, Peng; Xu, Dongdong; Wang, Ligai; Ding, Zhili; Shao, Qingjun (Frontiers in Marine Science, 2024)
Exploring alternatives to fishmeal (FM) in aquaculture nutrition remains a hot topic in this area. Yarrowia lipolytica (YL), a promising single-cell protein source, has yet to be evaluated for its use on the Pacific white shrimp (Litopenaeus vannamei) diet. This investigation assessed the effects of YL on growth performance, metabolism, antioxidant capacity, and nutrient digestibility in shrimp. Seven diets with equal protein and lipid contents were prepared, incorporating gradient YL (dry matter basis): 0% (control), 1.50%, 3.00%, 4.50%, 6.00%, 9.00%, and 12.00%. During a 56-day feeding trial involving shrimp, with an initial average weight of 0.32 ± 0.02 g, each kind of diet was randomly assigned to six tanks. It was observed that the growth performance improved initially but then exhibited a declining trend as the dietary inclusion of YL increased. Regression analysis indicated 2.68% as the optimal YL percentage for a specific growth rate (SGR), accounting for 10.54% of the dietary FM content. A higher YL (over 6.00%), which is equivalent to replacing over 23.6% of the FM, led to increased feed intake and conversion ratios, possibly correlating with decreased YL digestibility. However, YL inclusion across the studied range had no detrimental impact on intestinal or hepatopancreatic morphology. Notably, higher YL levels significantly enhanced hepatopancreatic trypsin activity and reduced serum triglyceride and cholesterol levels. The inclusion of YL notably augmented antioxidant defense mechanisms in shrimp, as evidenced by increased total antioxidant capacity and catalase activities, as well as reduced malondialdehyde levels in the hepatopancreas, possibly due to the presence of β-glucan and mannan oligosaccharides in YL. These findings support YL being viable as a protein source in shrimp feeds.